2013
DOI: 10.5152/balkanmedj.2013.9591
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in Breast Cancer: Predictors of Axillary and Non-Sentinel Lymph Node Involvement

Abstract: Background: Sentinel lymph node biopsy is a standard method for the evaluation of axillary status in patients with T1-2N0M0 breast cancers.Aims: To determine the prognostic significance of primary tumour-related clinico-histopathological factors on axillary and non-sentinel lymph node involvement of patients who underwent sentinel lymph node biopsy.Study design: Retrospective clinical study. Methods:In the present study, 157 sentinel lymph node biopsies were performed in 151 consecutive patients with early sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…Similarly to our findings, although on a slightly smaller scale a Turkish group [14] found that tumour size and lymphovascular invasion were significant primary tumour related prognostic determinants.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to our findings, although on a slightly smaller scale a Turkish group [14] found that tumour size and lymphovascular invasion were significant primary tumour related prognostic determinants.…”
Section: Discussionsupporting
confidence: 91%
“…Postacı et al 19 reported a close relationship between tumour size and axillary lymph node involvement. The risk of axillary lymph node metastasis increases as tumour size increases which suggests that nodal metastasis is indicative of tumour chronology20.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, while loss of Claudin-4 and other members of the Claudin family may facilitate invasion by increasing cell mobility, re-expression of Claudin-4 may confer survival advantages within host tissue, potentially by promoting cohesion in established metastases [ 18 ]. As these events are also related to tumor size [ 19 ], this might explain the finding of the significant association of Claudin-4 and larger tumor size.…”
Section: Discussionmentioning
confidence: 99%